(untitled) (Biological Sciences - PJSIR, 1994)
A pot experiment was carried out using sandy and calcareous soils to study the effects of gamma irradiating doses for sorghum seeds on dry matter yield and elemental uptake. Three cuttings were taken during the experiment every 40 days. Results showed that 4 Kr. dose was the best dose that caused significant higher increase of dry matter yield and nutrients uptake for three cuttings under both types of soil. Gamma irradiation doses at 8 Kr. and above all had an adverse affect on dry matter yield and nutrients uptake, especially under calcareous soil.